Synthesis and antimicrobial evaluation of cationic low molecular weight amphipathic 1, 2, 3-triazoles. Issue 5 (1st March 2017) - Bakka, Thomas A.; Strøm, Morten B.; Andersen, Jeanette H.; Gautun, Odd R.
Graphical abstract: Abstract: A library of 28 small cationic 1, 4-substituted 1, 2, 3-triazoles was prepared for studies of antimicrobial activity. The structures addressed the pharmacophore model of small antimicrobial peptides and an amphipathic motif found in marine antimicrobials. Eight compounds showed promising antimicrobial activity, of which the most potent compound10b displayed minimum inhibitory concentrations of 4–8 μg/mL against Streptococcus agalacticae, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Enterococcus faecalis . The simple syntheses and low degree of functionalization make these 1, 4-substituted 1, 2, 3-triazoles interesting for further optimizations.